MicroRNA gene dynamics in immune cell subpopulations during aging and atherosclerosis disease development at single-cell resolution - de Sande; Ana Hernández; Turunen, Tanja; Bouvy-Liivrand, Maria; Örd, Tiit; Palani, Senthil; Lahnalampi, Mari; Tundidor-Centeno, Celia; Liljenbäck, Heidi; Virta, Jenni; Niskanen, Henri; Jayasingha, Buddika; et al. (Springer Science and Business Media LLC, 2026)
Background: Regulatory networks controlling aging and disease trajectories remain incompletely understood. MicroRNAs (miRNAs) are a class of regulatory non-coding RNAs that contribute to the regulation of tissue homeostasis by modulating the stability and abundance of their target mRNAs. MiRNA genes are transcribed similarly to protein-coding genes which has facilitated their annotation and quantification from bulk transcriptomes. Here, we show that droplet, spatial, and plate-based single-cell RNA-sequencing platforms can be used to decipher miRNA gene signatures at cellular resolution to reveal their expression dynamics in vivo.
Methods: We first benchmarked the approach examining concordance between platforms, species, and cell type-specific bulk expression data. To discover changes in miRNA gene expression that could contribute to the progressive loss of cellular homeostasis during aging and disease development, we annotated the comprehensive aging mouse dataset, Tabula Muris Senis, with cell type-specific miRNA expression and acquired transcriptome and translatome profiles from an atherosclerosis disease model. Results: We generated an openly available workflow and aging-profile resource to characterize miRNA expression from single-cell genomics studies. Comparing immune cells in spleen tissue between young and old mice revealed concordance with previous functional studies, highlighting the upregulation of mmu-mir-146a, mmu-mir-101a, and mmu-mir-30 family genes involved in senescence and inflammatory pathways. Atherosclerosis progression is reflected within adipose tissue as expansion of the myeloid compartment, with elevated pro-inflammatory mmu-mir-511 expression in several macrophage subtypes. Upregulation of the immunosuppressive mmu-mir-23b ~ mir-24–2 ~ mir-27b locus was specific to Trem2 + lipid-associated macrophages, prevalent at late disease. Accordingly, ribosome-associated RNA profiling from myeloid cells in vivo validated significant mmu-mir-23b target gene enrichment in disease-regulated translatomes. Prominent tissue infiltration of monocytes led to upregulated mmu-mir-1938 and mmu-mir-22 expression and in classical monocytes activated mmu-mir-221 ~ 222, mmu-mir-511, and mmu-mir-155 gene loci, confirmed by bulk nascent transcriptomics data from ex vivo macrophage cultures. Overall, the monocyte-associated changes in miRNA expression represented the most significant target gene associations in the disease-trajectory translatome profiles.
Conclusions: We demonstrate that miRNA gene transcriptional activity is widely impacted in immune cells by aging and during disease development and further identify the corresponding translatome signature of inflamed adipose tissue.